From a Si3‐Cyclopropene to a Si3S‐Bicyclo[1.1.0]butane to a Si3S‐Cyclopropene to a Si3S2‐Bicyclo[1.1.0]butane: Back‐and‐Forth, and In‐Between. Issue 47 (25th September 2015) - Lee, Vladimir Ya.; Gapurenko, Olga A.; Miyazaki, Shogo; Sekiguchi, Akira; Minyaev, Ruslan M.; Minkin, Vladimir I.; Gornitzka, Heinz
Abstract: Compact and highly reactive bicyclo[1.1.0]butanes constitute one of the most fascinating classes of organic compounds. Furthermore, interplay of bicyclo[1.1.0]butanes with their valence isomers, such as buta‐1, 3‐dienes and cyclobutenes, is among the fundamental pericyclic transformations in organic chemistry. Herein we report the back‐and‐forth interconversion between the cyclotrisilenes and thiatrisilabicyclo[1.1.0]butanes, allowing for the synthesis of novel representatives of such classes of highly reactive organometallics. The peculiar structural and bonding features of the newly synthesized compounds, as well as the mechanism of their isomerization, were verified both experimentally and computationally. Abstract : Back‐and‐forth and in‐between : The back‐and‐forth interconversion between the cyclotrisilenes and thiatrisilabicyclo[1.1.0]butanes is presented, allowing for the synthesis of highly reactive organometallic compounds. The peculiar structural and bonding features of the newly synthesized compounds, as well as their isomerization mechanism, are verified both experimentally and computationally.